Pemanfaatan Teknologi Informasi dan Kompetensi Sumber Daya Manusia Terhadap Efektivitas Sistem Informasi Akuntansi: Studi Kasus pada PT. Karya Satria Advertising Semarang Tahun 2023 - Dewi, Vidia Suryani; Utomo, Riska Ayu Setyo; Indarti, Iin (STIE Widya Manggala, 2024)
This study aims to examine the use of information technology and human resource competence on the effectiveness of the accounting information system at PT. Karya Satria Advertising in 2023. The population and sample used is the finance and Accounting employees of PT. Works by Satria Advertising. The data source used is primary data obtained from questionnaires distributed to employees of the finance and accounting department. Sampling technique using non-probability sampling method. The analytical tool used is Multiple Linear Regression. The results of the study partially show that the use of information technology has a positive and insignificant effect on the effectiveness of accounting information systems, while the competence of human resources has a positive and significant effect on the effectiveness of accounting information systems. The results of the study simultaneously show that the use of information technology and human resource competencies have a significant positive effect on the effectiveness of accounting information systems. The coefficient of determination is 0.719 or 72% which indicates that the dependent variable, namely the Effectiveness of the Accounting Information System, is influenced by the two independent variables, namely Utilization of information technology and Human Resource Competence. While the remaining 28% is influenced by other factors.